The influence of non-governmental organizations (NGOs) on the development of voluntary sustainability accounting reporting rules - Sisaye, Seleshi (Journal of Business and Socio-economic Development, 2021)
PurposeThe purpose of this paper is to show the impact that non-governmental organizations (NGOs) have on the evolution of Global Reporting Initiative (GRI). GRI is a sustainability report disclosed by business organizations to meet the demands and interests of various stakeholders. These stakeholders’ needs have influenced GRI and its guidelines.Design/methodology/approachThe methodology for this paper is library-based archival research. It is qualitatively and analytically descriptive of prior academic research and published literature on the subject.FindingsSustainability accounting rulemaking has evolved overtime resulting in proliferation of reporting rules. These rules have improved the extent and scope of environmental and economic performances that businesses disclose in GRI.Originality/valueGRI has provided the foundation for integrated reporting (IR). Both GRI and IR have ecological and functional dimensions. Sustainability is functionally inherent in the accounting principle of materiality, when disclosed in external reporting. The ongoing concern of business assumes an organization is systemic and operates as a living entity only when it can provide sustainable performance that benefits stakeholders and society.